Anatomy of Conflict between Corporation and Local Community in a Geothermal Industry in West Java - Prayogo, Dody (UI Scholars Hub, 2010)
Relationship between corporation and local community in mining and oil industry in Indonesia has changed significantly since political reform (1998) and the enactment of regional autonomy (1999 and 2004). Social conflicts arouse as main symptom of such changes, that almost all corporations had common problems in their relationship with local communities. Based on previous studies, the anatomy of conflicts can be elaborated into three dimensions: causes, dynamics and resolution of conflict. Cause of conflict includes variables of political reform, inequality, exploitation, domination, empowerment, demographic and economic pressure; dimension of dynamics includes variables of fluctuation, escalation and type of conflict, role of actor and institution, and local cultural characteristics; and dimension of resolution consist of variables of old and new social contracts. With this framework this study analyses empirically the conflict between corporation and local community in Kecamatan Pangalengan, Kabupaten Bandung, West Java. The results indicate that there is a pattern of significance of causes, dynamics and resolution of conflicts, which is in general reveals a relation among dimensions of conflict.